MONITORING FOREST AREA CHANGE USING QUICKBIRD - Sri Endayani; Andrew Stefano; Fathiah Fathiah; Purbawati Purbawati; Ida Rosanti (BIOTROPIA, 2022)
A study was conducted to compare the urban forest management in three urban forests in Samarinda City. The application of GIS (Geographic Information System) is one of the alternatives to conduct a variety of processes such as: providing geographical information system, identifying the areas of urban forests in Samarinda, helping to plan the process of map digitalization and performing overlay process. The main method used for the data analysis process on the map was the overlay process data analysis technique. The research findings showed that: 1) the appointment of urban forests as the initial step of urban forest development needed more implementation from the government; 2) the urban forest determination needed more socialization to the owner of the urban forest and the public in 1992 and 2019; 3) the urban forests needed more management. There were some similarities and differences in the management of urban forests in the three study locations. The similarities among the three locations were that the three locations had already met the minimum standards of one urban forest location even though there was still one location outside of these three locations which did not meet the minimum standard. The differences were in managing the urban forests. These differences indicated that the urban forest policy was not fully implemented in Samarinda City.